Asia‐inclusive drug development leveraging principles of ICH E5 and E17 guidelines: Case studies illustrating quantitative clinical pharmacology as a foundational enabler - Hong Lu; Lena Klopp‐Schulze; Jatinder Kaur Mukker; Dandan Li; Yoshihiro Kuroki; Jayaprakasam Bolleddula; Nadia Terranova; Kosalaram Goteti; Wei Gao; Rainer Strotmann; Jennifer Dong; Karthik Venkatakrishnan (Clinical and Translational Science)
Abstract With the International Conference on Harmonization of Technical Requirements for Pharmaceuticals for Human Use (ICH) E17 guidelines in effect from 2018, the design of Asia‐inclusive multiregional clinical trials (MRCTs) has been streamlined, thereby enabling efficient simultaneous global development. Furthermore, with the recent regulatory reforms in China and its drug administration joining the ICH as a full regulatory member, early participation of China in the global clinical development of novel investigational drugs is now feasible. This would also allow for inclusion of the region in the geographic footprint of pivotal MRCTs leveraging principles of the ICH E5 and E17. Herein, we describe recent case examples of model‐informed Asia‐inclusive global clinical development in the EMD Serono portfolio, as applied to the ataxia telangiectasia and Rad3‐related inhibitors, tuvusertib and berzosertib (oncology), the toll‐like receptor 7/8 antagonist, enpatoran (autoimmune diseases), the mesenchymal–epithelial transition factor inhibitor tepotinib (oncology), and the antimetabolite cladribine (neuroimmunological disease). Through these case studies, we illustrate pragmatic approaches to ethnic sensitivity assessments and the application of a model‐informed drug development toolkit including population pharmacokinetic/pharmacodynamic modeling and pharmacometric disease progression modeling and simulation to enable early conduct of Asia‐inclusive MRCTs. These examples demonstrate the value of a Totality of Evidence approach where every patient's data matter for de‐risking ethnic sensitivity to inter‐population variations in drug‐ and disease‐related intrinsic and extrinsic factors, enabling inclusive global development strategies and timely evidence generation for characterizing benefit/risk of the proposed dosage in Asian populations.